Quo Vadis Islamic Multicultural Education: Reorienting the Paradigm Toward Peaceful Living in an Era of Global Polarization - Sundari Sundari; Maskuri Maskuri (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
The growing polarization caused by identity conflicts, digital misinformation, and social fragmentation has challenged the role of Islamic education in promoting peaceful coexistence. This study aims to reconstruct the paradigm of Islamic multicultural education by proposing a new conceptual orientation toward peaceful living. Employing a qualitative Systematic Literature Review (SLR) based on the PRISMA 2020 framework, this study synthesized recent scholarly publications (2021–2025) on Islamic multicultural education, multiculturalism, peace education, and social cohesion. The findings reveal that contemporary Islamic multicultural education should move beyond tolerance-based approaches toward a transformative paradigm that integrates Islamic values with peace education. This article proposes the Peaceful Living-Oriented Islamic Multicultural Education Framework (PLIME Framework), which positions justice, tolerance, moderation, consultation, balance, brotherhood, and compassion as foundational values implemented through curriculum, dialogical pedagogy, inclusive leadership, institutional culture, and community engagement. The framework contributes theoretically by integrating Islamic education, multicultural education, and peace education into a comprehensive model for fostering ethical consciousness, dialogue, collaboration, social cohesion, and a sustainable culture of peace in increasingly polarized societies.